ANALISIS KEBUTUHAN PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO PEMBELAJARAN PADA MATA KULIAH PEMECAHAN MASALAH - Muhammad Ali; Radiatul Adawiah; Sri Juniati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
This research is motivated by students' difficulties in understanding problem solving material and knowing the peraepsi / presumption of lecturers and students. Therefore, research on the development of learning video-based teaching materials in the form of problem solving textbooks was carried out. The purpose of this study was to find out how the perceptions / assumptions of lecturers and students on teaching materials in the form of learning videos-based textbooks. This research is a development research using ADDIE development model. The subject of this research was the STKIP Paris Barantai 5th semester mathematics education program students. Data obtained through interviews, questionnaires, and observations. Data analysis techniques were carried out in a qualitative descriptive way. The results of the study of the needs analysis of learning video-based teaching materials found that: (1) Lecturers in the much needed category were 5 people or 71.42% and Needed as many as 2 people 28.57%, (2) Students in the category desperately needed as many as 22 people or 88%, it takes as many as 3 people 12%. The conclusion of this study is learning video-based teaching materials in mathematics problem solving courses are needed by lecturers and students. Keywords: Needs Analysis, Teaching Materials, Problem Solving.